Finite Dimensional Uniform Attractors for the Nonautonomous Camassa-Holm Equations. (20th July 2009) - Wu, Delin
Abstract : We consider the uniform attractors for the three-dimensional nonautonomous Camassa-Holm equations in the periodic box Ω = [ 0, L ] 3 . Assuming f = f ( x, t ) ∈ L loc 2 ( ( 0, T ) ; D ( A − 1 / 2 ) ), we establish the existence of the uniform attractors in D ( A 1 / 2 ) and D ( A ) . The fractal dimension is estimated for the kernel sections of the uniform attractors obtained.